Micro-Scale Abrasive Wear Testing of CrN Duplex PVD Coating on Pre-Nitrided Tool Steel - Mercado-Solis,Rafael David (2017)
Specific wear rates were calculated from a series of micro-scale abrasive tests by means of the calotte-grinding method. The tested material was a CrN coating deposited by arc evaporation on ion-nitrided AISI H13 steel. Characterizations included: phase analysis, chemical composition, metallography, microhardness, micro-scratch resistance and nano-indentation hardness. On wear testing, the counter body was a 30 mm diameter steel ball rotating at a tangential speed of 9.42 m/min and normal load of 0.54 N. The abrasive was a mono-crystalline diamond micro abrasive paste, 1 micrometer grit. Wear volumes were calculated by measuring the wear scars at various test intervals. In non-perforating tests, Archard's wear equation was directly employed for calculating coating wear rate as the slope of the linear least square data fit. In perforating tests, Allsopp's method was employed for the simultaneous determination of coating and substrate wear rates, from the slope and intercept values of the linear least square data fit. Coating specific wear rate values obtained from both non-perforating and perforating tests were very consistent, with a relative difference within 6%. Relative errors in specific wear rate values were estimated to be of the order of 0.05 for the coating and 0.2 for the substrate.